Titanium‐Mediated Addition of Grignard Reagents to Acyl Cyanohydrins: Aminocyclopropane versus 1, 4‐Diketone Formation. Issue 1 (29th October 2013) - Setzer, Paul; Forcher, Gwénaël; Boeda, Fabien; Pearson‐Long, Morwenna S. M.; Bertus, Philippe
Abstract: The 1, 2‐dianion reactivity of the reagent generated from EtMgBr and titanium isopropoxide was illustrated when N ‐acyl cyanohydrins were used as substrates (>20 examples), giving both aminocyclopropane derivatives and 1, 4‐dicarbonyl compounds. When the reaction was performed in diethyl ether, 5‐hydroxy‐1, 4‐diketones were the main product. Under specific conditions (use of tetrahydrofuran and a bulky carboxylic moiety), the cyclopropane derivatives were obtained in good yields. The observed dichotomy may be explained by a ring‐opening of the five‐membered titanacycle intermediate followed by a nonselective acyl addition. Abstract : The 1, 2‐dianion reactivity of the reagent generated from EtMgBr and Ti(O i Pr)4 was illustrated when N ‐acyl cyanohydrins were used as substrates (>20 examples). When the reaction was performed in diethyl ether, 1, 4‐diketones were mainly isolated. Under certain conditions, cyclopropane derivatives were also obtained in good yields. A mechanism rationalizing this dichotomy is presented.